Sepsis favors high-on-clopidogrel platelet reactivity. (2nd January 2018) - Akinosoglou, Karolina; Perperis, Angelos; Theodoraki, Spyridoula; Alexopoulos, Dimitrios; Gogos, Charalambos
Abstract: High-on-treatment platelet reactivity (HPR) is associated with ischemic events in patients on antiplatelet therapy with a history of cardiovascular disease. On the other hand, recent data have associated sepsis with adverse cardiovascular events in patients admitted with bacteremia or respiratory infection. We aimed to assess P2Y12 -mediated platelet reactivity (PR) during sepsis and recovery in patients under clopidogrel. This was a prospective observational study. Incoming patients presenting with signs/symptoms of sepsis already on a maintenance dose of clopidogrel of 75 mg qd for cardiovascular events were included in this study. Patients were assessed for their PR on presentation and following septic syndrome, using the VerifyNow point-of-care P2Y12 assay. Patients were excluded in the presence of evidence of noncompliance to antiplatelet regimen or in need of discontinuation during this study. Twenty-two septic patients on clopidogrel were included in this study (Supplemental Figure S1). Clopidogrel was administered for previous stroke, coronary, and peripheral artery disease in 27.3, 40.9, and 31.8% of patients, respectively. The main site of infection was respiratory tract followed by urinary tract, while the same amounts of gram-negative and -positive pathogens were isolated. HPR was noted in 77% and 29% of patients during sepsis and recovery, respectively, presenting a significant decrease in P2Y12 reaction units values during follow-up [240.7 ± 58.3 versus 179.5 ± 58.4, 95% CI (–102.7, –39.76), p = 0.0002]. Five patients died of infection, while no adverse cardiovascular events were noted in our study. Our study shows that sepsis may favor HPR, which is reversed when recovery occurs. This finding may underlie the adverse cardiovascular events in patients admitted with sepsis, possibly requiring alteration of antiplatelet regimen during the inflammation period.